Does the halal label of Lemonilo instant noodles matter to students? - Saadah, Ni’matus; Mawadah, Sokhikhatul; Fauzi, Muhammad (Asian Journal of Islamic Management (AJIM), 2023)
Purpose – This study aimed to determine the influence of the Korean wave, brand ambassadors, and halal label on the purchasing decisions of Lemonilo instant noodles.Methodology – This study uses quantitative research methods. Using a purposive sampling technique, the research sample comprised 72 students from a management study program at UIN Walisongo Semarang. Descriptive statistical analysis, a validity test, a reliability test, a classical assumption test, multiple linear regression analysis, and hypothesis testing were used.Findings – The Korean wave variable positively and significantly influenced purchasing decisions. By contrast, brand ambassadors and halal label had an insignificant effect on the purchasing decisions of Lemonilo instant noodles among students of the Management Study Program at UIN Walisongo Semarang.Implications – Literacy of the halal label among the student community needs to be enhanced to understand that the halal label is an essential aspect in deciding food consumption. Additionally, it needs to be understood that the Korean wave is not always in line with Islamic values; therefore, an understanding of the halal label is necessary within the young community familiar with the Korean wave..Originality – This study aims to determine the extent of the influence of the Halal label on students in Islamic institutions regarding their decision to purchase Korean instant noodle products